(untitled) (Comparative Professional Pedagogy, 2025)
The article is devoted to the comparative analysis of methods used to control and assess academic achievements of undergraduates majoring in Software Engineering at universities of Ukraine and the United Kingdom. In the context of the dynamic development of the information society and rapid changes in the labor market, the issue of effective assessment of acquired knowledge and practical skills is becoming increasingly relevant. The study examines the theoretical foundations of the development of control and assessment systems in higher education in both countries, identifies the regulatory and legal framework for organizing the assessment process, particularly under national educational standards and international recommendations. Special attention is paid to the role of assessment as a tool for developing professional competencies necessary for successful activity in the field of information technologies. Through comparative analysis, common features and differences in the approaches to assessing the learning outcomes of Software Engineering undergraduates are revealed, particularly regarding the use of traditional and innovative assessment methods aimed at evaluating both academic knowledge and practical skills in software design, development, and testing. The paper substantiates the advantages of using practice-oriented assessment methods that simulate real-world production processes and formulates recommendations for modernizing the national system of academic achievement assessment based on the best practices of British higher education. It is determined that British universities ensure high pedagogical transparency through a clear distinction between forms of control and assessment methods, which are reflected in program documents in accordance with QAA standards. This approach promotes the development of a competency-based approach, a focus on real-life professional conditions, and the formation of academic integrity. The results of the study can be used to further optimize the content of educational programs and to improve forms of control and assessment methods, taking into account the development trends of the global IT industry.